Mechanisms for the Confiscation of Illegal Profits in Environmental Criminal Law Enforcement Based on the Polluter Pays Principle in Indonesia - Karlin Z. Mamu; Sri Olawaty DJ. Suaib; Melki T. Tunggati (VRISPRAAK : International Journal of Law, 2026)
Environmental crimes have become one of the most economically profitable crimes globally, but the Indonesian environmental criminal law system has not been able to reach the dimension of financial gains obtained by perpetrators illegally. Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) contains fundamental weaknesses at the level of formulation policy, namely the lack of a clear and operational mechanism to confiscate illicit gains in environmental criminal law enforcement, so that the polluter pays principle mandated by Article 2 letter j of the UUPPLH only functions as a declarative principle without real operational power. This study aims to analyze the weaknesses of the UUPPLH formulation in regulating the mechanism for confiscating illegal profits and formulate an ideal regulatory construction so that all economic benefits from pollution can be internalized effectively. Using normative legal research methods with statutory, conceptual, and comparative approaches, this study found that the UUPPLH does not regulate the formula for calculating illicit gains, does not require the calculation of the economic benefit of noncompliance in prosecution, and does not provide a non-conviction-based asset forfeiture (NCBA) mechanism for environmental crimes. The proposed ideal construction is built on three pillars: a substantive pillar in the form of a lex specialis norm that defines illicit gains comprehensively, a procedural pillar in the form of an obligation to calculate and prove illicit gains in every prosecution, and an institutional pillar in the form of synergy between the Attorney General's Office's Asset Recovery Agency and the Ministry of Environment and Forestry and the establishment of an Environmental Trust Fund as an exclusive vehicle for ecological recovery.